Design and Implementation of an X-Band 1-Bit Reconfigurable Transmitarray System with a Space-Time Coding Scheme - Sung-Geon Kim; Inhwan Kim; Youngjae Yu; Ic-Pyo Hong; Kyung-Won Lee; Sunghun Jung; Myung-Sik Lee; Jong-Gwan Yook (Journal of Electromagnetic Engineering and Science)
This paper proposes a 1-bit reconfigurable transmitarray system operating in the X-band that is capable of implementing a space-time coding scheme. The proposed transmitarray consists of a 10×10 array of unit cells, each exhibiting high transmission performance and offering precise 1-bit phase resolution. To enable the application of the space-time coding scheme, an FPGA-based control board is designed to ensure fast and accurate independent control of all unit cells. The proposed structure is designed using full-wave simulations and then fabricated for practical implementation, with measurements confirming the realization of active and harmonic beam steering through the implementation of the space-time coding scheme.